Analysis and Evaluation Methods of Seismic Subsidence Characteristics of Loess and Field Seismic Subsidence - Yan, Xiaotong; Wang, Shun; Wang, Ningwei (Earth Sciences Research Journal, 2021)
The objective of this research is to analyze the dynamic degeneration of loess and the evaluation method of field seismic subsidence. In this study, Q3 loess is taken as the research object, and the dynamic properties of loess with 10%, 20%, 30% and 35% moisture content are tested by triaxial experiment. In addition, seismic subsidence characteristics of loess with dry densities of 1.4g/cm3, 1.6g/cm3, and 1.8g/cm3 and consolidation stress ratios of 1.0, 1.2, 1.4, and 1.6 are analyzed. Then the simplified seismic subsidence estimation method is used to calculate the relationship between seismic subsidence coefficients at different soil depth in one dimensional field, cycle times, and subsidence depth. The results show that the higher the water content of loess is, the greater the change of seismic subsidence appears. The larger the dry density of loess is, the smaller the change degree of seismic subsidence appears. The larger the consolidation stress ratio is, the greater the change of seismic subsidence occurs in loess. When the depth of soil reaches 9.5m, the maximum seismic subsidence coefficient can reach 0.8%. When the depth of soil layer is 10m, the degree of seismic subsidence is the largest. When the depth of soil layer is 12~16m, the settlement depth caused by earthquake subsidence is small. While the depth of soil layer is 8~12m, the settlement degree is large.